Crisis music : The cultural politics of Rock Against Racism - Goodyer, Ian (Book collections on Project MUSE., 2009)
Marching to the beat of punk rock and reggae, Rock Against Racism was a mass movement built in opposition to racism and fascism in 1970s Britain. At a time of severe economic and social crises, RAR, alongside the Anti-Nazi League, organised one of the biggest and most effective political and cultural mobilisations of the post-war period. Expressing itself through spectacular carnivals, concerts, marches and innovative forms of design and communication, RAR combined hard-headed political organisation with the optimism and energy of radical youth culture. Drawing on interviews with activists, supp.